The influence of El Niño and edge effects on the reproductive phenology and floral visitors of Eschweilera tetrapetala Mori (Lecythidaceae), an endemic species of the Atlantic Forest of northeastern Brazil - Isiara Silva Menezes; Ana Paula Lima do Couto-Santos; Ligia Silveira Funch (Acta Botânica Brasílica, 2017)
ABSTRACT We compared the reproductive phenology and floral visitors of Eschweilera tetrapetala growing along the edge and in the interior of a submontane forest in the Chapada Diamantina mountains, Bahia State, Brazil. We sought to determine if there were inter-annual differences in intensity and seasonality associated with environmental conditions, and if there were differences in floral visitors between the two environmental contexts. Phenological observations were performed for three years, and included the occurrence of an El Niño event. We applied circular statistics to detect seasonal trends, performed cross correlations between phenophases and climate, Kruskal-Wallis and Wilcoxon signed-rank tests for inter-annual variation, and the Wilcoxon-Mann-Whitney test for edge-interior differences in the species richness of floral visitors. We observed inter-annual variations in the intensity and seasonality of flower production that accompanied variations in rainfall, possibly associated with El Niño events. Floral visitor richness differed between the forest edge and interior, with seven species recorded for the interior and only one for the edge. Reduced fruit set was also observed at the forest edge. This study contributes to our understanding of the influence of El Niño and edge effects on the reproductive phenologies of tropical plants.